Regional Inequalities in the Availability of Equipment, Supplies and Specialized Reference in Oral Radiology in Brazilian Primary Health Care - Manoelito Ferreira Silva-Junior; Felipe Bittarello; Vitória Monteiro; Pollyana Kassia de Oliveira Borges; Marcia Helena Baldani (Pesquisa Brasileira em Odontopediatria e Clínica Integrada)
Objective: To analyze the availability of equipment, supplies and specialized reference in oral radiology in primary care health by comparing Brazilian geographic regions. Material and Methods: The time series analysis was carried out with secondary data extracted from official databases of the Brazilian Ministry of Health of the external evaluation cycles of the National Program for Improvement of Access and Quality of Primary Health Care (PMAQ-AB). The comparisons of Brazilian regions were performed using Chi-square and Z tests adjusted by the Bonferroni method, and among cycles (years) using the Cochran's Q test (p<0.05). Results: In Brazil, there was an increase in the availability of X-ray equipment between 2014 and 2018 (21.9% vs. 36.3%), and supplies where there was X-ray equipment, which included lead aprons (75.6% vs. 86.4%), dark chamber (darkroom) (86.4% vs. 93.9%) and chemical products for the X-ray film processing (80.7% vs. 86.1%) (p<0.001). The specialized reference in oral radiology was higher in 2018 (71.4%) compared to 2012 (46.8%) and 2014 (66.9%) (p<0.001), with the same trend in the Northeast region (p<0.001). North and Northeast showed growing numbers for most items evaluated, with a reduction in regional inequalities. Conclusion: The availability of equipment, supplies, and specialized reference among Brazilian regions increased. Although regional inequalities persist in Brazil, a reduction was observed in the analyzed period.